2021
DOI: 10.1021/acs.inorgchem.0c03241
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyl Defects in LiFePO4 Cathode Material: DFT+U and an Experimental Study

Abstract: Lithium iron phosphate, LiFePO4, a widely used cathode material in commercial Li-ion batteries, unveils a complex defect structure, which is still being deciphered. Using a combined computational and experimental approach comprising density functional theory (DFT)+U and molecular dynamics calculations and X-ray and neutron diffraction, we provide a comprehensive characterization of various OH point defects in LiFePO4, including their formation, dynamics, and localization in the interstitial space and at Li, Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…The LFP crystal structure is formally represented as a hexagonal oxygen close-packing where Li is located in edgesharing octahedra (the M1 site) and Fe is positioned in cornersharing octahedra (the M2 site). 5 This structure easily accommodates various point defects: lithium (V Li ) and iron (V Fe ) vacancies, Fe Li and Li Fe antisite pairs, hydroxyl defects associated with the P substitution, or a combination of these, [7][8][9][10] with all of them drastically influencing the electrochemical performance. 11 The antisite defects are the most abundant due to their low formation energy.…”
Section: Introductionmentioning
confidence: 99%
“…The LFP crystal structure is formally represented as a hexagonal oxygen close-packing where Li is located in edgesharing octahedra (the M1 site) and Fe is positioned in cornersharing octahedra (the M2 site). 5 This structure easily accommodates various point defects: lithium (V Li ) and iron (V Fe ) vacancies, Fe Li and Li Fe antisite pairs, hydroxyl defects associated with the P substitution, or a combination of these, [7][8][9][10] with all of them drastically influencing the electrochemical performance. 11 The antisite defects are the most abundant due to their low formation energy.…”
Section: Introductionmentioning
confidence: 99%
“…To estimate the change of the oxygen chemical potential (Δμ­(O)) corresponding to the conditions of LCO deposition at a finite temperature T (K) and oxygen partial pressure p (atm) we used the following equation where Δ H (O 2 , T , JANAF) and Δ S (O 2 , T , JANAF) are the change of both enthalpy and entropy according to the temperature and obtained from the JANAF thermochemical table, and RT ln p (O 2 ) is the contribution of O 2 partial pressure. Note that we used the JANAF database implemented as a python-based package Thermochem ().…”
Section: Experimental and Theoretical Sectionmentioning
confidence: 99%
“…explored anionic redox chemistry in a Co‐free and Li‐rich layered cathode material, Li 1.2 Ni 0.2 Mn 0.6 O 2 . [ 4d ] They reported that cationic Ni 2+ oxidation, followed by a series of oxygen‐related oxidation and/or extraction steps resulted in a charge capacity of 0.97e – /formula unit. Despite the promised effectiveness of these inorganic cathodes, their intrinsic characteristics do not allow for fast charging/discharging cycles and the use of these materials is also not sustainable.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] In an effort to improve the energy‐storage capability of Li‐ion batteries, inorganic cathode materials have been widely studied, from conventional transition metal oxides (i.e., LiCoO 2 , LiFePO 4 , and LiMn 2 O 4 ) and mixed‐metal oxides (i.e., Ni‐Mn‐Co oxides, namely NMC) to Li‐rich inorganic cathodes with an anionic redox process. [ 4 ] For instance, Luo et al. explored anionic redox chemistry in a Co‐free and Li‐rich layered cathode material, Li 1.2 Ni 0.2 Mn 0.6 O 2 .…”
Section: Introductionmentioning
confidence: 99%